Islamic motivation in the framework of the idea "Mangilik el" (Eurasian Journal of Religious Studies, 2021)
This article presents the development of a national mentality and values that combine traditional and religious beliefs, as well as the motivational concept of Islam. This issue is currently not sufficiently studied. It is extremely important to use the theory of knowledge to stimulate the needs and desires of representatives of society, linking the requirements of the "Koran" and Sharia with modern requirements, to develop a special level of thinking and reasoning that contributes to their promotion. To solve this problem, was done work on the review and study of literature, scientific journals and online sources. For the reliability of the research, information from the "Koran" itself was used. In the course of the study, we pay special attention to the fact that Islam is a value reference point. To summarize, Allah created people to "recognize and keep His words". For this, he offers a certain reward. However, the thought of not following his instructions causes fear. However, this thesis provides a deeper understanding of the role of Islam in the pursuit of a healthy and meaningful life on earth and in the afterlife. The expected result manifests itself as soon as you establish knowledge and understanding of human aspiration and behavior.Key words: “Mangilik el”, motivation, creative thinking, Maslow’s theory, time management.
Keywords: Spiritual rebirth; motivation; creative thinking; Maslow's theory; time management